Odpowiedzi

Najlepsza Odpowiedź!
2009-09-29T19:55:57+02:00
(2x+y)²-(x+y)(3x-2y)-3xy =4x²+4xy+y²-(3x²-2xy+3xy-2y²)-3xy=
=4x²+4xy+y²-3x²+2xy-3xy+2y²-3xy=x²+3y²
x=-10 i y=1/3
x²+3y²
(-10)²+3(1/3)²=100+3*1/9=100+1/3=100 i 1/3
8 4 8
2009-09-29T22:15:38+02:00
(2x+y)²-(x+y)(3x-2y)-3xy =4x²+4xy+y²-(3x²-2xy+3xy-2y²)-3xy=
=4x²+4xy+y²-3x²+2xy-3xy+2y²-3xy=x²+3y²
x=-10 i y=1/3
x²+3y²
(-10)²+3(1/3)²=100+3*1/9=100+1/3=100 i 1/3
5 3 5
2009-09-29T22:27:12+02:00
(2x+y)²-(x+y)(3x-2y)-3xy =
=4x²+4xy+y²-(3x²-2xy+3xy-2y²)-3xy=
=4x²+4xy+y²-3x²+2xy-3xy+2y²-3xy=
=x²+3y²

x=-10
y=1/3
x²+3y²
(-10)²+3(1/3)²=100+3*1/9=100+1/3=100 i 1/3
3 2 3